ANALISIS POSTUR KERJA PADA OFFICER DAN ADMIN DIVISI LOGISTIK PT XYZ DENGAN METODE CMDQ DAN ROSA - Sasson, Putera; Budiawan, Wiwik (Industrial Engineering Online Journal, 2024)
Abstrak Ergonomi perkantoran adalah penerapan ilmu ergonomi yang meliputi keseluruhan lingkungankerja dan alat kerja yang digunakan, seperti perangkat komputer dan kursi. Bahaya umum diperkantoran biasanya disebabkan oleh postur kerja yang tidak baik, gerakan repetitif, dan posisistatis yang dikerjakan dalam durasi yang lama. Cedera yang paling sering dihadapi adalahMusculoskeletal Disorders (MSDs). Penelitian ini akan menganalisis postur kerja officer dan adminDivisi Logistik PT XYZ untuk mengetahui bahaya postur kerja mereka dalam menimbulkan risikoMSDs. Metode yang digunakan dalam penelitian ini adalah Cornell Musculoskeletal DiscomfortQuestionnaires (CMDQ) sebagai scanning awal dan Rapid Office Strain Assessment (ROSA)sebagai instrumen penilaian office ergonomics. Berdasarkan hasil kuesioner CMDQ yang telahdilakukan, didapatkan keluhan tertinggi terdapat pada bagian lower back, hip/buttoks, dan neck. Berdasarkan hasil rekapitulasi ROSA didapatkan postur kerja dengan tingkat risiko berbahayadialami oleh CS Admin Logistik, Officer Logistik, Admin Logistik 2, dan Admin Logistik 3. Masingmasingmemperolehskor7,8,6,dan6.Sementaraitu,AdminLogistik1memilikiposturkerjayangberadapadaambangbatastidakberbahaya,yaituskor5.BerdasarkanhasilmetodeCMDQdanROSA,rekomendasiperbaikanyangdiberikanberupausulanpenggantianfasilitasdanperubahanposturkerja.Kata kunci: CMDQ, ergonomi perkantoran, MSDs, postur kerja, ROSAAbstract [Title: Working Posture Analysis of Logistics Divison Officers and Admins at PT XYZ UsingCMDQ and ROSA] Office ergonomics is the application of ergonomics which covers the entirework environment and work tools used, such as computers and chairs. Common hazards in officesare usually caused by poor working posture, repetitive movements, and static positions that are heldfor a long duration. The most common injuries are Musculoskeletal Disorders (MSDs). This studywill analyze the working postures of officers and admins of the Logistics Division of PT XYZ to findout the dangers of their work postures in causing the risk of MSDs. The methods used in this studywere the Cornell Musculoskeletal Discomfort Questionnaires (CMDQ) as the initial scanning andthe Rapid Office Strain Assessment (ROSA) as an office ergonomics assessment instrument. Basedon the results of the CMDQ questionnaire that was carried out, the highest complaints were foundin the lower back, hip/buttocks, and neck. Based on the results of the ROSA recapitulation, theworking posture with a dangerous level of risk was experienced by Logistics Admin CS, LogisticsOfficer, Logistics Admin 2, and Logistics Admin 3. Each received a score of 7, 8, 6, and 6.Meanwhile, Logistics Admin 1 has working posture that is at the non-hazardous threshold, namelya score of 5. Based on the results of the CMDQ and ROSA methods, recommendations forimprovement are in the form of proposed replacement of facilities and changes to work postures.Keywords: CMDQ, MSDs, office ergonomics, ROSA, working posture